2020
DOI: 10.1007/978-3-030-58144-2_21
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Memory Anomalies in OpenMP Applications

Abstract: Incorrect usage of OpenMP constructs may cause different kinds of defects in OpenMP applications. Most of the existing work focuses on concurrency bugs such as data races and deadlocks, since concurrency bugs are difficult to detect and debug. In this paper, we discuss an under-examined defect in OpenMP applications: memory anomalies. These occur when the application issues illegal memory accesses that may result in a non-deterministic result or even a program crash. Based on the latest OpenMP 5.0 specificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…However, concurrency bugs and performance issues may still arise due to incorrect usage of device directives. Our group at Georgia Tech has conducted a comprehensive study of such issues [141]. We found that most of these issues are related to the data mappings between the host and target device.…”
Section: Wbs 23211 Building Tools To Detect and Debug Bugs And Perfor...mentioning
confidence: 99%
“…However, concurrency bugs and performance issues may still arise due to incorrect usage of device directives. Our group at Georgia Tech has conducted a comprehensive study of such issues [141]. We found that most of these issues are related to the data mappings between the host and target device.…”
Section: Wbs 23211 Building Tools To Detect and Debug Bugs And Perfor...mentioning
confidence: 99%